Islamic Banking, Political Economy, and Financial Development: A Bibliometric Mapping of Global Research Trends Using VOSviewer - Reni Marlina; Lilis Sakuroh; Erry Hendriawan (ITB AAS INDONESIA Surakarta, 2026)
This study aims to analyze the global research trends on Islamic banking, political economy, and financial development using a quantitative bibliometric approach. Data were collected from the Scopus database, covering 541 publications published between 2010 and 2025. The dataset was analyzed using VOSviewer to identify the intellectual structure, thematic evolution, and research gaps within the field. The results show a total of 15,632 citations, with an average of 28.88 citations per document and an h-index of 52, indicating a strong academic impact. Keyword co-occurrence analysis identified 104 significant keywords (minimum occurrence: 5), forming five major clusters, with dominant themes including Islamic banking (178 occurrences), financial development (132), and economic growth (119). The network visualization reveals a total link strength exceeding 3,400, reflecting a highly interconnected research structure. Density visualization confirms that financial development and banking performance are the most concentrated research areas, while political economy and innovation-related themes remain less explored. Furthermore, overlay visualization indicates a temporal shift toward emerging topics such as fintech (average year 2022.6), sustainability (2021.9), and ESG (2023.1), although their occurrence levels remain relatively low (12–28). These findings suggest that while Islamic banking has been extensively studied in relation to financial growth, the integration of political economy perspectives and technological innovation is still limited. This study contributes by providing a comprehensive mapping of research trends and identifying critical gaps for future investigation, particularly in strengthening interdisciplinary linkages to support sustainable financial development.